Conducta oposicionista desafiante y su influencia en la relación con sus pares - Ube Plaza, Holger Fabian (2020)
This present case study, in which the oppositional defiant behavior and its peer influence was investigated in which it was noted that the negative behaviors demonstrated with the patient influences his relationship with his peers, where this prevents him from enhancing the daily activities within The school, due to its challenging, unreasonable, socially inadequate form against the authority figures within the educational community, through the clinical interview, it was found that because in its family environment it sees different mistreatments, from there it acquired these challenging behaviors. This patient presented the criteria for the diagnosis according to the DSM-V, for the defiant negativist disorder, for the observation of their parents' behaviors in their home, where abuse, physical and psychological manifests and this displacing them to school with their classmates and teachers, psychotherapy is provided to reduce these behaviors and thoughts goals were also set according to the patient's problems for a good prognosis.